Predicting Hedge Fund failure : the role of risk across time - Gaspar, Francisco Guilherme Nazaré (2015)
This study focuses on the relation between the risk profile of a hedge fund and its probability to fail. We propose to model the failure event using survival analysis through a Cox Hazards Model while incorporating piecewise effects in the risk covariate. Empirical results suggest that there has been a shift in the relationship between the risk profile of a hedge fund and its probability of failure. For the period between 1995 and 2006, larger risk was associated with higher probability of failure whereas since 2007, increasing risk levels reduce the risk of failure of hedge funds. We are the first to show this effect and use this model in Hedge Funds literature. These findings allow investors to better understand the dynamics of risk and probability to fail and may have huge implications in portfolio composition.